Evaluating the Availability of Ulipristal Acetate in Eastern Long Island [15F]. (May 2018) - Korotkaya, Yelena; Schmidt, Elizabeth
Abstract : INTRODUCTION: Ulipristal acetate (UPA) was approved by the FDA in 2010 as a form of emergency contraception (EC), which can be taken within 120 hours of unprotected sex. Evidence has shown that UPA is more effective than oral levonorgestrel emergency contraceptive pills (LNG-ECP) and more cost effective. UPA is more effective in patients with a BMI >30. No studies have looked at the availability of UPA in New York State. We specifically looked at Long Island due to its population density. METHODS: We conducted an observational population-based study utilizing a telephone-based secret shopper methodology. Researchers called 200 unique retail pharmacies in Long Island from May 2016-July 2017, representing themselves as patients and physicians. RESULTS: Only 9.5% of pharmacies had UPA immediately available, although 81% reported ability to order UPA. In contrast, 80% reported having LNG-ECP readily available. Only 47% of pharmacists who had UPA available could correctly identify its differences from LNG-ECP. 82% of pharmacists in the physician call group were unfamiliar with UPA. In addition, 0% of pharmacists mentioned BMI as an important difference in efficacy between UPA and LNG-ECP. CONCLUSION: Although UPA is the more effective EC than LNG-ECP, its availability is limited. Knowledge of UPA is lacking in pharmacists and clinicians alike. Increasing education of clinicians, pharmacists and patients regarding differences between EC pills may assist in increasing demand for UPA and could increase overall availability of UPA.